Autecology of Capparis spinosa Linn. in Cold Desert of Spiti Valley in Himachal Pradesh - Singh, R P; Bahar, Nav; Chand, Prakash (Annals of Arid Zone, 2016)
Capparis spinosa Linn. is a dominant trailing shrub of cold desert of Spiti Valley in. Himachal Pradesh. Its seed has hard seed coat dormancy which can be overcome by concentrated sulphuric acid (H2SO4) treatment and mechanical scarification. Root system contributes maximum (65.33%) to the total biomass followed by aboveground biomass (34.66%). It covers 4.24 m2 areas of soil by aerial portion. Root of single plant can bind soil upto 3.43 m2 with the strong lateral roots. The taper rate varies from 0.42 to 1.04 which itself is an indication of strong root system.